PENDAMPINGAN PENGEMBANGAN EKONOMI KREATIF PRODUK OLAHAN JAHE SEBAGAI UPAYA PENINGKATAN EKONOMI MASYARAKAT - Farsya Ashila Yumna; Muhammad Mufid; Bakhrul Ulum; Ati Dinan Nasihah; Nilna Munalkarima; Rizky Nur Maghfiroh (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2023)
Empowerment of Jam'iyah women in Jurangmangu Village. Pulosari District. Pemalang Regency, were relatively low. Community service activities were carried out regarding assistance in developing the creative economy of processed ginger products as an effort to improve the community's economy. The creative economy is an action to create added value obtained from the creativity of human resources, knowledge, culture and technology, one of which is creating processed ginger products, so that it can increase the selling value in the form of instant products rather than raw ginger, making it easier to consume, as well as optimizing the potential and quantity availability of ginger. The method of implementing activities is in the form of counseling and training methods. The results of the outreach activities and ginger powder training showed that participants can understand processed ginger products that can be developed into home businesses, so that they can generate additional income. Therefore, through this community service activity the potential of Jurangmangu Village, Pulosari District on natural resources, namely ginger, so that they can be used to improve the economy of village communities. Apart from that, the positive response seen and the public's assessment of the product is one of the successes of this activity. For this reason, it is hoped that the implementation of this activity can improve the community's economy from these processed products.